2015
DOI: 10.1371/journal.pone.0139170
|View full text |Cite
|
Sign up to set email alerts
|

SATB1 Mediates Long-Range Chromatin Interactions: A Dual Regulator of Anti-Apoptotic BCL2 and Pro-Apoptotic NOXA Genes

Abstract: Aberrant expression of special AT-rich binding protein 1 (SATB1), a global genomic organizer, has been associated with various cancers, which raises the question of how higher-order chromatin structure contributes to carcinogenesis. Disruption of apoptosis is one of the hallmarks of cancer. We previously demonstrated that SATB1 mediated specific long-range chromosomal interactions between the mbr enhancer located within 3’-UTR of the BCL2 gene and the promoter to regulate BCL2 expression during early apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…However, inhibition of SATB1 cleavage by caspase-6 inhibitor led to an increase in BCL2 expression and decrease in NOXA transcription [104]. Thus increase in SATB1 levels, may potentially disrupt the equilibrium of the apoptotic regulatory genes and may contribute to cancer development and progression.…”
Section: Satb1 and Apoptosis In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…However, inhibition of SATB1 cleavage by caspase-6 inhibitor led to an increase in BCL2 expression and decrease in NOXA transcription [104]. Thus increase in SATB1 levels, may potentially disrupt the equilibrium of the apoptotic regulatory genes and may contribute to cancer development and progression.…”
Section: Satb1 and Apoptosis In Cancermentioning
confidence: 99%
“…Likewise, SATB1 induced epigenetic modification of BCL2 promoter enables binding of the transcription factor CREB to BCL2 promoter and positively regulates BCL2 expression [103]. SATB1 also regulates the expression of the proapoptotic gene NOXA via the mbr enhancer [104]. Transcription of BCL2 and NOXA genes depends on their interaction with mbr enhancer.…”
Section: Satb1 and Apoptosis In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that over‐expression of SATB1 alters the expression of a large number of genes in a cell‐specific manner (Purbey et al , ; Tan et al , ; Oda et al , ; Yang et al , ). Initially, researches were restricted in immune cells (Kumar et al , ; Ahlfors et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…SATB1 and SATB2 can also form heterodimers to regulate gene expression [19,46]. It is also well-known that SATB1 can mediate long-range chromatin interactions for gene regulation [4,47,48]. Thus, ELF5…”
Section: Satb1 Is An Essential Regulator Of T Cell Differentiation Anmentioning
confidence: 99%